The SME-suitable industry reservation policy: Economic effects and policy direction - Minho Kim (Korea Development Institute (KDI), 2022)
After marking the ten-year milestone since the adoption of the SME-suitable industry reservation policy, this study investigates whether the policy has enhanced the competitiveness of SMEs by safeguarding them as intended and offers implications for its future implementation. This SME policy involves the selection of specific products to protect the business territories of SMEs and limit the entry or expansion of large enterprises; however, evidence-based discussions on its effectiveness have been limited. While the production and employment of large businesses decreased after the adoption, the business activities of SMEs did not change much. This reservation policy aimed to "ensure the competitiveness of SMEs through their protection." It successfully fulfilled its protective role by reducing the likelihood of SMEs exiting the market. However, the reservation policy had limited impact in terms of improving their performance or competitiveness. Following the designation of a set of industries (products) reserved for SMEs, the probability of exit for SMEs engaged in the production of those specific products significantly decreased. However, these SMEs did not show significant differences compared to other product producers in terms of most performance and input indicators. The industry-level analysis shows that the policy contributed little to the performance of overall industries to which the designated products belong. The disappointing outcomes of the policy's stringent measures highlight its limited effectiveness, as the restrictions on the expansion or entry of large enterprises did not lead to significant improvements in the performance of SMEs. Based on the findings, it is recommended to suspend new applications for the designation of SME-suitable industries and gradually phase out the already designated reserved industries. In any business field, when there is greater uncertainty about future market restrictions, firms are less incentivized to engage in that market and invest in domestic production facilities. A policy that restricts production activity in a specific business area solely based on firm size may inadvertently undermine the efficiency of resource allocation in the broader economy. Instead of protecting specific business areas, a win-win policy between SMEs and large firms should prioritize providing effective support for the growth of capable SMEs through appropriate regulatory measures to address anti-competitive and unfair practices.
Keywords: 330